(untitled) (Research, Society and Development, 2021)
In 2012, with the Berenice Piana Law, discussions began about the achievements of people with Autism Spectrum Disorder (ASD), who have conquered their space in the labor market, but the stigma of disability ends up hindering this evolution. To contribute to and disseminate the factors that affect the effective social inclusion of autistic people in the labor market, research has been presented in this direction. The aim of this study is to measure and compare the professional productive capacity of people with ASD versus a Neurotypical person (person considered normal or without autistic characteristics), taking as a case contracting companies of this workforce. For this purpose, an exploratory and quantitative approach of a basic nature was carried out. The finding was that the restrictions imposed by ignorance of autistic ability insure the maximum or ideal use of the abilities of people with ASD. However, when oriented and in the functions in which their skills/competencies can be revealed, they have an equal or higher productivity index when compared to neurotypical people.